Method to investigate the short-term effects of vibration on the output performance of the proton exchange membrane fuel cell in fuel cell vehicles. (1st October 2022) - Nan, Zequn; Behrendt, Matthias; Bause, Katharina; Albers, Albert; Wei, Xuezhe; Ma, Tiancai; Lin, Weikang; Zuo, Shuguang
Highlights: Vibration measurements and analysis of powertrain components and the FC in FCVs. Quantitative analysis of the contribution of components to the vibration of the FC stack. Analysis of the vibration effect on FC performance by in-situ FC vibration test. Abstract: The proton exchange membrane fuel cell (PEMFC) in fuel cell (FC) vehicles (FCVs) is always operating in a vibration environment, which can affect the FC output performance. This effect will bring new challenges in terms of NVH (Noise, Vibration and Harshness) and should be investigated during the development of FCVs. This paper proposes an investigation method for the short-term effect of vibration on the output performance of the FC in FCVs. The method is generalized as a procedure with four stages. Firstly, the vibrations of powertrain components and FC are measured by performing measurements on overall FCV, considering different driving maneuvers and environments. The characteristics of components' vibrations are then identified and the vibration environment of the FC in the FCV is investigated by conducting vibration and contribution analysis. The analysis results are used to derive the vibration cases for the in-situ FC vibration test in the last stage to investigate the vibration effect on the FC performance. In general, vibration reduces the output power of FC by about 2% compared to the case without vibration. The fluctuation of FC power under vibration is also increased. Different FC orientations can also affect its performance, and this effect can be enlarged when vibrations are introduced. In the worst case, vibration can cause a power reduction of more than 9%. In addition, the sensitivity of the FC output power to different types of excitation varies. The knowledge obtained during the investigation provides the basis for the NVH development and optimization with the aim of improving FC output performance.